Emotional awareness for fun digital communication - Yeyentimalla, Yeyentimalla (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2022)
Improving digital communication skills is a necessity in the era of information technology, especially during the COVID-19 pandemic, and after the pandemic has passed, this need remains. We have to adjust or we fall behind. In digital communication we must strengthen the skills of stringing words, that's the only effective way to share ideas and feelings. Humans are emotional creatures. We always feel first than we think about our feelings. The alignment of impulses in the brain reaches the limbic system first, we feel. Then the impulses are processed in the cerebri cortex, we become able to think about our feelings. It's important to be able to do emotional animation consciously. Emotional animation is an attempt to bring to life positively valued emotions such as pleasure, relief, compassion, empathy, gratitude, etc., and controlling negatively valued emotions such as anger, sadness, hate, disgust, etc. We need to improve communication skills to level four, which are safe and comfortable sharing feelings. The comfort of speaking to share feelings is the result of being created, not happening unconsciously. It's important to be aware when speaking. The most visible technique that can be trained is confirmation. Confirmation is effective for careful linking with partners. This editorial provides examples communication through chatting application Whatsapp. What about the availability of emoticons and stickers in the WhatsApp platform? Can't it be used to replace intonation and body language? It can indeed be used in the right situations so as to strengthen the words. However, overuse of emoticons and stickers makes messages less personal. We also become less than optimal in the way we are present and respond to the presence of others. Finally, the way we communicate is rooted in character, but character formation takes a long time. Being aware to do emotional animation in every conversation is a simple short-term solution in fixing communication problems. In digital communication, making optimal the ability to string words is the right choice.